'At risk' positioning and hip biomechanics of the peewee ice hockey sprint start. Issue 4 (27th March 2011) - Philippon, M J; Stull, J D; LaPrade, R F
Abstract : Background: 'At risk' motion of the hip is defined primarily by internal rotation during flexion, reportedly increasing vulnerability to labral injury and observed during the recovery phase of the adult ice hockey skating stride. No biomechanical analysis has focused on 'at risk' hip motion in youth hockey players sprint starts. Objective: To investigate the biomechanics of the male youth ice hockey sprint start with attention to the hip and a previously identified 'at risk' position. We hypothesised that youth hockey players display 'at risk' hip motion during the sprint start. Design: Descriptive in vivo laboratory study. Setting: The study was conducted in a biomechanics laboratory on 6.4 mm acrylic surface manufactured specifically for ice hockey skate testing. Participants: 12 healthy male Peewee ice hockey players (mean age: 10.8 (± 0.6 years)). Assessment of risk factors: Participants were assessed for hip flexion at maximum internal rotation by 10 high-speed infrared cameras that recorded 35 anatomical identifiers to assess the 3-D biomechanics of the ice hockey sprint start over 100 time-segments comprising the sprint stride. Main outcome measurements: Data was collected for hip flexion, extension, abduction, adduction, external and internal rotation. Results: During the recovery phase of the sprint start, maximum internal rotation in each hip occurred simultaneously to that hip approaching maximum flexion (Push leg; 5.6° internal rotation with 44.2° flexion; Lead leg; 10.8° internal rotation with 35.1° flexion). As the sprint start progressed, 'at risk' motion was increasingly exaggerated by increased hip rotation speed (Lead leg;+2.7° flexion/time-segment during recovery phase over the final 14% of the sprint). Conclusion: During the sprint start, youth ice hockey players internally rotate while proceeding through hip flexion, displaying 'at risk' hip motion. This knowledge could be applied with related future findings to aid potential prevention of hip overuse injuries as youth hockey players mature and increase in skill level.